A kinetic and kinematic comparison of the two-footed and step-out back handsprings on the balance beam - Ede, C. J.; Yeadon, M. R.; Hiley, M. J. (Sports Biomechanics, 2024)
The back handspring is one of the most commonly performed skills on the balance beam in women's gymnastics. Despite this, quantitative research on the beam has often been overlooked. This study aimed to investigate the kinetic and kinematic variables during the performance of two back handspring techniques on the beam: the back handspring with two footed landing and the back handspring step-out. A modified balance beam was fixed to a force plate with an isolated mat for landing to allow analysis of the take-off and hand contact phases. Kinetic and kinematic data were recorded for twelve gymnasts performing both techniques. No statistically significant differences between techniques were found during take-off. However, average peak vertical and horizontal ground reaction forces (4.1 bodyweights ± 1.1 BW, and 0.7 BW ± 0.2 BW, respectively) were higher and time to peak force shorter during the hand contact phase for the two footed variant. A more vertical trajectory, along with a greater hand contact ground reaction force were found in comparison to the back handspring performed on the floor. These results highlight the need for more specific investigation to understand the factors which could contribute to reducing the load faced during balance beam performance.